Use of Wild Type or Recombinant Lactic Acid Bacteria as an Alternative Treatment for Gastrointestinal Inflammatory Diseases: A Focus on Inflammatory Bowel Diseases and Mucositis - Carvalho, Rodrigo D. De Oliveira; do Carmo, Fillipe L. R.; de Oliveira Junior, Alberto; Langella, Philippe; Chatel, Jean-Marc; Bermúdez-Humarán, Luis G.; Azevedo, Vasco; de Azevedo, Marcela S. (Frontiers in Microbiology, 2017)
The human gastrointestinal tract (GIT) is highly colonized by bacterial communities, which live in a symbiotic relationship with the host in normal conditions. It has been shown that a dysfunctional interaction between the intestinal microbiota and the host immune system, known as dysbiosis, is a very important factor responsible for the development of different inflammatory conditions of the GIT, such as the idiopathic inflammatory bowel diseases (IBD), a complex and multifactorial disorder of the GIT. Dysbiosis has also been implicated in the pathogenesis of other GIT inflammatory diseases such as mucositis usually caused as an adverse effect of chemotherapy. As both diseases have become a great clinical problem, many research groups have been focusing on developing new strategies for the treatment of IBD and mucositis. In this review, we show that Lactic Acid Bacteria (LAB) have been capable in preventing and treating both disorders in animal models, revealing to be useful for clinical treatment. In addition, we present the most current studies on the use of wild type or genetically engineered LAB strains designed to express anti-inflammatory proteins as a promising strategy in the treatment of IBD and mucositis.